Kepemimpinan Interpersonal dan Implementasinya di Lembaga Pedidikan - May Sarah (JURNAL EDUKASI NONFORMAL, 2021)
An institution certainly needs a leader who has a leadership spirit. This is because one of the things that has a significant impact on a team's ability to achieve its goals is leadership. The power possessed by a leader greatly affects others in the scope of his work. Having the ability to lead and influence subordinates and assign tasks to be done is called power. This study aims to determine the implementation of interpersonal leadership in educational institutions. This research is a qualitative research using library research data collection techniques by reading, reviewing, and documenting various literatures or reading materials relevant to the subject matter, which are then filtered and compiled into a theoretical framework. The data analysis used is content analysis is a type of research that requires an in-depth examination of the information content. interpersonal communication has an impact on organizational performance and behavior, according to the findings. Interpersonal communication has four components: (1) dissipating ideas, (2) admonishing and disciplining subordinates, (3) communicating messages, and (4) familiarity with subordinates. Communication has an impact on organizational performance, can offer feedback to improve employee performance, can communicate company goals to subordinates, and can influence interaction and communication between leaders and subordinates. Through individual and collective contributions, this pattern will have an impact on improving teacher performance in the organization. The implementation of interpersonal communication in the world of education can be done by the principal. Positive interpersonal communication can affect the structure of communication exchanges between leaders and subordinates in order to improve organizational performance and in school institutions the principal is fully responsible for advancing the school, improving the performance of teachers and employees, and realizing an effective school.